PENGARUH KUALITAS LAPORAN KEUANGAN, KOMPLEKSITAS PEMERINTAHAN, DAN TINGKAT KESEJAHTERAAN DAERAH TERHADAP TINGKAT PENGUNGKAPAN SUKARELA INFORMASI KEUANGAN PADAWEBSITE PEMERINTAH DAERAH (STUDI KASUS PEMERINTAH DAERAH TINGKAT PROVINSI SE – INDONESIA) - Yulia Yustikasari (Jurnal Riset Akuntansi Terpadu, 2018)
This study aims to examine the Quality of Regional Government, Government Complexity, and Regional Welfare Levels affecting the Level of Voluntary Disclosure of Financial Information on Local Government Websites. The testing of the effect of independent variables on the dependent variable used multiple linear regression equations and using cross section data. The results of testing the hypotheses provide evidence that the variable quality of local government does not affect the level of voluntary disclosure of financial information on local government websites, other than that for government complexity variables have a significant effect on the level of voluntary disclosure of financial information on local government websites, while for variable welfare level Regions do not influence the Level of Voluntary Disclosure of Financial Information on Local Government Websites.